2015
DOI: 10.1016/j.clml.2015.02.021
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II, Single-Arm, Open-Label, Multicenter Study to Evaluate the Efficacy and Safety of P276-00, a Cyclin-Dependent Kinase Inhibitor, in Patients With Relapsed or Refractory Mantle Cell Lymphoma

Abstract: Overexpression of cyclin D1 is a hallmark feature of mantle cell lymphoma (MCL). Many of the oncogenic effects of cyclin D1 are mediated through cyclin dependent kinases (CDKs). P276-00 is a potent small-molecule inhibitor of CDK4-D1, CDK1-B, and CDK9-T with promising activity in pre-clinical models. In Phase I studies of P276-00 in patients with refractory solid neoplasms, it was well-tolerated with a mild trend of single-agent efficacy. A Phase II study of this agent was conducted in patients with relapsed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 21 publications
2
33
0
Order By: Relevance
“…Taken together, our studies suggest that CDK9 might be a novel therapeutic target in synovial sarcomas, perhaps most effective in combination with apoptosis‐inducing cytotoxic chemotherapy . Indeed, similar combinations are currently under investigation in clinical trials for the treatment of hematological cancers . However, similar clinical trials have not yet been reported in solid tumors, including synovial sarcomas.…”
Section: Discussionmentioning
confidence: 65%
“…Taken together, our studies suggest that CDK9 might be a novel therapeutic target in synovial sarcomas, perhaps most effective in combination with apoptosis‐inducing cytotoxic chemotherapy . Indeed, similar combinations are currently under investigation in clinical trials for the treatment of hematological cancers . However, similar clinical trials have not yet been reported in solid tumors, including synovial sarcomas.…”
Section: Discussionmentioning
confidence: 65%
“…Rohitukine, a plant-derived chromone alkaloid, is the precursor of the promising anticancer clinical candidates flavopiridol (also known as alvocidib, HMR 1275, L86-8275) [ 222 , 223 , 224 ] and P276-00 [ 223 , 225 ]. However, the antitumor activity, pharmacokinetics, and CDK inhibitory potential of this parental product were not studied in detail for a long time.…”
Section: Cdk Inhibition In Pdacmentioning
confidence: 99%
“…Nerviano Medical Sciences, Nerviano, Italy Metastatic solid tumors [27,28] Cyclin E and CDK-2 Cyclin A and CDK-2 LY2835219 Cyclin D and CDK-4/6 Eli Lilly, Indianapolis, IN, United States Lung cancers [29] LEE011 Cyclin D and CDK-4/6 Novartis, Basel, Switzerland Gastrointestinal cancers [30] Breast Cancer [31] AZD5438 Cyclin D and CDK-4/6 Astra Zeneca, London, England Solid malignancies [32] Cyclin E and CDK-2 Cyclin A and CDK-2 Cyclin A and CDK-1 BAY 1000394 Cyclin D and CDK-4/6…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, CDK4 overexpression is linked to a poor prognosis in colorectal cancer [26] . From the list of inhibitors currently in clinical trials, found in Table 1 [23, [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] , there have been a few that have been studied more specifically in colorectal cancer. One that has shown particular promise is PD-0332991, from Pfizer, New York, NY.…”
Section: Cancermentioning
confidence: 99%